Impact of polymorphisms in genes orchestrating innate immune responses on replication kinetics of Torque teno virus after kidney transplantation - Redondo, Natalia; Rodríguez-Goncer, Isabel; Parra, Patricia; Albert, Eliseo; Giménez, Estela; Ruiz-Merlo, Tamara; López-Medrano, Francisco; San Juan, Rafael; González, Esther; Sevillano, Ángel; Andrés, Amado; Navarro, David; et al. (Frontiers in Genetics, 2022)
Background: Torque teno virus (TTV) DNAemia has been proposed as a surrogate marker of immunosuppression after kidney transplantation (KT), under the assumption that the control of viral replication is mainly exerted by T-cell-mediated immunity. However, Tthe impact on post-transplant TTV kinetics of single genetic polymorphisms (SNPs) in genes orchestrating innate responses remains unknown. We aimed to characterize the potential association between 14 of these SNPs and TTV DNA levels in a single-center cohort of KT recipients. Methods: Plasma TTV DNAemia was quantified by real-time PCR in 221 KT recipients before transplantation (baseline) and regularly through the first 12 post-transplant months. We performed genotyping of the following SNPs: CTLA4 (rs5742909, rs231775), TLR3 (rs3775291), TLR9 (rs5743836, rs352139), CD209 (rs735240, rs4804803), IFNL3 (rs12979860, rs8099917), TNF (rs1800629), IL10 (rs1878672, rs1800872), IL12B (rs3212227) and IL17A (rs2275913). Results: The presence of the minor G allele of CD209 (rs4804803) in the homozygous state was associated with undetectable TTV DNAemia at the pre-transplant assessment (adjusted odds ratio: 36.96; 95% confidence interval: 4.72–289.67; p-value = 0.001). After applying correction for multiple comparisons, no significant differences across SNP genotypes were observed for any of the variables of post-transplant TTV DNAemia analyzed (mean and peak values, areas under the curve during discrete periods, or absolute increments from baseline to day 15 and months 1, 3, 6 and 12 after transplantation). Conclusion: The minor G allele of CD209 (rs4804803) seems to exert a recessive protective effect against TTV infection in non-immunocompromised patients. However, no associations were observed between the SNPs analyzed and post-transplant kinetics of TTV DNAemia. These negative results would suggest that post-transplant TTV replication is mainly influenced by immunosuppressive therapy rather than by underlying genetic predisposition, reinforcing its clinical application as a biomarker of adaptive immunity.